Impairment of visual object-discrimination learning after perirhinal cortex ablation. - Buckley, M; Gaffan, D (1997)
Eight cynomolgus monkeys learned preoperatively 20 concurrent visual discriminations between pairs of colored shapes presented on a touch screen with 24-hr intertrial intervals. Three then received bilateral perirhinal cortex ablation, and 5 remained controls. The ablated monkeys were severely impaired in reacquiring the preoperatively acquired set, whereas postoperative learning of 20 new discriminations was not significantly affected. The task was then made more difficult. First, the number of foils from which the stimulus had to be selected was increased to 2, 4, 7, and then 14. Second, larger sets of 40, 80, and 160 problems were presented. Both manipulations revealed some significant but relatively mild impairments in the monkeys with ablations. It is suggested that perirhinal cortex ablation impairs the monkey's capacity to identify individual objects, which leads to deficits in both visual-object recognition memory and discrimination learning.